PENERAPAN MANAJEMEN MUTU TERPADU (TQM) DAMPAK DAN SOLUSINYA - Tri Winarti; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The quality achievement of an educational institution can be determined in various ways, one of which is based on an integrated quality management approach/Total Quality Management (TQM). This research aims to describe the implementation of integrated quality management at SDI Al Azhar xx. The research uses a qualitative approach with descriptive methods. The data collection techniques used were observation, interviews and documentation studies. The research subjects were school principals, teachers and students. The results of the research show: (1) The implementation of integrated quality management really helps schools in efforts to improve quality, (2) In implementing integrated quality management, the school principal involves all school personnel, (3) In efforts to improve quality it is seen from the aspects of service, human resources , the environment, learning process, and products (graduates) of SDI Al Azhar xx are good, (4) The impact that arises from the implementation of integrated quality management is the high educational costs that must be paid by parents of students so that schools must be very clever in setting strategies in PPDB, (5) the solution is to expand the PPDB publication and schedule the PPDB time earlier.